Political Connection And Real Earnings Management: The Moderating Role Of Audit Quality And Foreign Ownership - Fanya Jihan; Doddy Setiawan; Y Anni Aryani (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose – This study investigate the relationship between politically connected boards (PC) (both boards of directors [BODs] and supervisory boards [SBs]) and real earnings management (REM). This paper also discuss about the moderating role of audit quality (AQ) and foreign ownership (FO) on relationship between PC and REM. Methodology/approach – Quantitative research approach using data collection from annual reports and financial reports of listed manufacturing firm on the Indonesia Stock Exchange (IDX) for the last 3 years, from 2020 to 2022. Findings - The results showed that politically connected boards of directors and commissioners have a positive effect on real earnings management. Meanwhile, high audit quality and foreign share ownership as moderation can reduce earnings management behavior. The results support agency theory that political connections increase agency problems through earnings management practices, and good corporate governance suppresses management's deviant behavior Practical implications - The practical implications of this research include improving the quality of audits and internal controls, periodic checks, communication, reporting, and future research directions in the field of management control. These implications can be utilized by practitioners, organizations, shareholders, and researchers in avoiding earnings management behavior. Originality/value - The originality and novelty of this research lies in the addition of good corporate governance variables, foreign ownership as moderating variables